Serious Games Adaptation According to the Learner’s Performances - Amine Belahbib; Lotfi Elaachak; Mohamed Bouhorma; Othman Bakkali Yedri; Slimani Abdelali; Elouaai Fatiha (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Basically, serious games provides enjoyment and knowledge, several researches in this field have focused into joining these two proprieties and make the best balance between them, in order, to provide the best game and enjoyable game experience and ensure the learning of the needed knowledge. Players differ and their knowledge background can be a lot different from one to the other. This study focused on how the SG adapts and provide the needed knowledge and enjoyment. The game should analyze players behavior from different angles, thus it can add difficulty, information, immersion or enjoyment modules to fit the player skills/knowledge.